Evaluación Financiera para el Supermercado Galtor de la Ciudad de Loja, período 2013-2014 - Alverca Peña, Leidy Leonor (2016)
The thesis entitled "FINANCIAL ASSESSMENT FOR SUPERMARKET GALTOR LOJA CITY, PERIOD 2013-2014" was held in order to obtain the title of Engineer in Accounting and Auditing, developed according to the Academic Regulation Scheme the National University of Loja and to meet the economic and financial situation Supermarket, and was developed to meet the overall objective is: Perform a financial evaluation in Galtor Supermarket City of Loja, in 2013-2014. To meet the first specific objective is: Perform financial structure by applying the vertical analysis to evaluate each of the accounts of assets, liabilities and equity, income, costs, expenses and net income of the financial statements for the period 2014 the horizontal analysis to determine increases and decreases that have affected accounts in the periods 2013-2014 and financial indicators, such as liquidity, activity, profitability and debt to verify the operation of each of the accounts that make states financial. The second objective is: Perform the cash budget, the pro forma financial statements and applying indicators, such as the Net Present Value (NPV) Rate Interne of Return (IRR), Cost-Benefit and Sensitivity Analysis to meet this purpose the method of percentage change of monthly historical sales for the period 2014 was applied; allowing to perform preliminary calculations 6 up to the presentation of the Budget Cash and Proforma Financial Statements which served to calculate indicators Financial Assessment as: NPV was $ 214,785.39; Capital Recovery Period 11 months, 1 day TIR is equal to 112.45%; Sensitivity analysis Cost Benefit 0.98 and $ 1.03 which means that the reinvestment of utility is feasible to do it. The ultimate goal is: to present the report of the whole process of the Financial Evaluation Manager Owner for decision making to improve the economic and financial management Galtor Supermarket. For the development of the thesis first was the collection of information and observation operations carried out within the supermarket Galtor, which served to focus the study of Financial Evaluation allowed to examine the financial statements through the vertical analysis , horizontal and financial indicators and finally indicators of financial evaluation that helped make the management of the accounts that make up the financial statements in the periods studied where they could organize, summarize and interpret the established quantitative data, and then to suggest main conclusions and recommendations to the Manager-Owner for the benefit and development of Galtor Supermarket. Among the most notable findings from the Financial Assessment is the financial analysis allowed to verify the operation of each of the accounts that 7 make up the financial statements, then the cash budget and pro forma financial statements which served to implement the indicators was made like Net (NPV), Payback Period Capital, Internal rate of Return (IRR) Present Value, Cost-Benefit and Sensitivity Analysis and so it is recommended that this process Financial evaluation in the Supermarket Galtor of city of Loja, period 2013-2014 with their respective economic report and improvement strategies for will be taken into account by the owners to help them improve the economic, administrative and financial position in the local market.